Is health impact assessment useful in the context of trade negotiations? A case study of the Trans Pacific Partnership Agreement. Issue 4 (4th April 2016) - Hirono, Katherine; Haigh, Fiona; Gleeson, Deborah; Harris, Patrick; Thow, Anne Marie; Friel, Sharon
Abstract : Objective: The Trans Pacific Partnership Agreement (TPP) is a recently concluded free trade agreement involving Australia and 11 other Pacific-rim nations, which has the potential for far-reaching impacts on public health. A health impact assessment (HIA) was carried out during the negotiations to determine the potential future public health impact in Australia and to provide recommendations to mitigate potential harms. This paper explores the findings and outcomes of the HIA, and how this approach can be used to provide evidence for public health advocacy. Design: A modified version of the standard HIA process was followed. The HIA was led by technical experts in HIA, trade policy, and health policy, in collaboration with advocacy organisations concerned with the TPP and health. The HIA reviewed the provisions in leaked TPP text in order to determine their potential impact on future health policy. As part of this process, researchers developed policy scenarios in order to examine how TPP provisions may affect health policies and their subsequent impact to health for both the general and vulnerable populations. The four policy areas assessed were the cost of medicines, tobacco control, alcohol control and food labelling. Results: In all areas assessed, the HIA found that proposed TPP provisions were likely to adversely affect health. These provisions are also likely to more adversely affect the health of vulnerable populations. Conclusions: The HIA produced relevant evidence that was useful in advocacy efforts by stakeholders, and engaging the public through various media platforms.